FREQUENCY OF ANEMIA IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS IN TERTIARY CARE HOSPITAL KARACHI - Azizullah Khan Dhiloo1 Saleemullah Abro2, Quratulain Saleem 3, Nazima Zain 4, Khalil Ahmed Memon5, Amanullah Abbassi 6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
INTRODUCTION: Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory disease due to smoking. It is avertable as well as treatable. The COPD is a one of the leading cause of morbidity and mortality affecting globally. OBJECTIVE: To evaluate the Frequency of anemia in chronic obstructive pulmonary disease patients in tertiary care hospital Karachi. burden of anemia in chronic obstructive pulmonary disease patients at a tertiary care hospital Karachi. METHODS: This is a descriptive cross sectional study, done at JPMC Karachi in 2014. All COPD patients admitted in medicine and pulmonology departments were enrolled in this study. After informed consent, data of complete blood count was accessed from medical record and anemia was labeled as per operational definition. Data analyzed by SPSS version 16.0. Frequency and percentage proportion of qualitative variables, mean and standard deviation of numerical values were calculated with significant values (P- value <0.05). RESULTS: Of 137 cases, 118(86.13%) were males and 19(13.87%) were females while gender based ratio was 6.2: 1. The average age (58.31±12.17 years), average weight (59.36±10.56kg), average duration of disease (5.69±4.42 years) and average hemoglobin (12.34±1.58 mg/dl) of the patients respectively. The 37.96% (52/137) patients were anemic in our study. Rate of anemia in COPD patients was not significant among age groups (p=0.076) and with duration of disease (p=0.22).